Terrazzo for combined layer and preparation method of terrazzo
By introducing components such as modified cellulose ether and polycarboxylic acid water reducer into terrazzo materials, its sag resistance and mechanical properties are improved, and the performance of existing terrazzo materials in the design of special-shaped components and complex decorative structures is solved. The problem of insufficient results has achieved excellent performance and wider application in high slopes and complex facade structures.
Patent Information
- Application Number
- CN202411690965.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
AI Technical Summary
The existing terrazzo materials have insufficient anti-sag performance, mechanical properties and durability in the design of special-shaped components and complex decorative structures, which limits their application in the field of decoration-structure integrated design.
A terrazzo material for combined layers is used, and its formulation includes white cement, silicon micro powder, calcium and silicon mineral blend, white quartz sand, coarse aggregate, alkali-resistant glass fiber, toner, modified cellulose ether and defoaming Components such as agents can improve the material's anti-sag properties and mechanical properties through the cross-linking reaction of modified cellulose ether and the use of polycarboxylic acid water reducing agent.
It has achieved excellent sag resistance of terrazzo materials on high slopes and complex facade structures, improved its 28d compressive strength and bending performance, and maintained no peeling in 200 freeze-thaw cycles, significantly broadening its decoration - Application in the field of structural integrated design.
Smart Images

Figure BDA0005150930120000061 
Figure BDA0005150930120000071 
Figure HDA0005150930130000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a combined layer terrazzo and a preparation method thereof. Background Art
[0002] Traditional terrazzo is a product made of one or more aggregates and binders as the main raw materials, and is obtained by surface grinding and polishing. Due to its excellent decorative effect, it is often used in decorative design. The production process of terrazzo is mainly divided into two methods: pressing molding and integral casting molding. However, the material itself has low strength and has certain limitations in the field of decoration with irregular shapes and many curved surfaces, as well as in structural design.
[0003] Patent application CN 115093638 A discloses a plastic terrazzo material, wherein dry opaque plastic, elastomer, transparent plastic, and effect material are filled into a mold separately or mixed and then filled into a mold, and the plastic terrazzo material is obtained by hot pressing and cooling with the cooperation of a limit frame. Although this method has plasticity and certain light transmittance, its strength and wear resistance are poor, and it is difficult to use it in the field of outdoor decoration, and its application is greatly limited. Patent application CN108656309 A discloses a production method of special-shaped terrazzo with UHPC as a bonding material, wherein aggregate is pasted on the surface of the mold, and then the special-shaped terrazzo product is obtained by casting and molding with high-flow UHPC as a bonding material. Although the high-flow UHPC material used in this method can solve the production difficulties of some special-shaped components, it still has great limitations in the production of some special-shaped components with high slopes or even facades that require high anti-sagging performance of the material, as well as complex and diverse decoration-structure integrated designs. Summary of the invention
[0004] The main purpose of the present invention is to provide a composite layer terrazzo decorative layer material and a preparation method thereof in view of the problems and shortcomings of the prior art. The terrazzo decorative layer material has excellent anti-sagging performance, mechanical properties and durability, and has certain thixotropy. It is suitable for the design of various types of facades and various curved surfaces with special-shaped composite layer structures, and can effectively broaden the application of terrazzo in the field of decoration-structure integrated design.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A combined layer terrazzo comprises the following components and their weight proportions: 750-850 parts of white cement, 100-160 parts of silicon micropowder, 150-220 parts of calcium silicon mineral admixture, 900-1100 parts of white quartz sand, 100-120 parts of coarse aggregate, 5-10 parts of alkali-resistant glass fiber, 10-100 parts of color powder, 170-200 parts of water, 4-6 parts of modified cellulose ether, 1-1.5 parts of defoaming agent and 25-35 parts of polycarboxylic acid water reducing agent; the modified cellulose ether is borate cross-linked modified cellulose ether.
[0007] In the above scheme, the cellulose ether can be selected from hydroxyethyl methyl cellulose ether or hydroxypropyl methyl cellulose ether.
[0008] In the above scheme, the preparation steps of the modified cellulose ether are as follows:
[0009] (1) firstly adding cellulose ether into water, adding a catalyst and stirring at room temperature, then adding a borate-based crosslinking agent and heating to carry out a crosslinking reaction; then adjusting the pH value of the resulting solution system to be neutral or weakly alkaline;
[0010] (2) The mixed solution obtained from the above reaction is aged and filtered, and the filter cake is collected and washed with alcohol, dried to constant weight, ground and sieved to obtain powdered modified cellulose ether.
[0011] According to the above scheme, the catalyst can be selected from sodium carbonate or sodium hydroxide.
[0012] According to the above scheme, the mass ratio of the introduced catalyst to the cellulose ether is 1:3-6.
[0013] Furthermore, the catalyst is introduced in the form of an aqueous solution.
[0014] According to the above scheme, the borate-based cross-linking agent can be boric acid or borax.
[0015] According to the above scheme, the temperature used for the cross-linking reaction is 50-60°C and the time is 2-4h.
[0016] According to the above scheme, the pH value is 7-8.
[0017] According to the above scheme, the aging time is 16-24h.
[0018] According to the above scheme, the screening is through a 200-mesh sieve.
[0019] According to the above scheme, the mass ratio of the cellulose ether to the borate-based crosslinking agent is 10:(0.6-0.8).
[0020] According to the above scheme, the white cement is white silicate cement, the strength grade is not less than 52.5, and the whiteness is ≥84%.
[0021] According to the above scheme, the activity index of the silicon micropowder is greater than 105%, the whiteness is greater than 87%, and the SiO2 mass content is greater than or equal to 92%.
[0022] According to the above scheme, the calcium-silicon mineral admixture is formed by mixing 325-mesh heavy calcium and quartz powder in a mass ratio of (1-2):1.
[0023] According to the above scheme, the white quartz sand is mixed by 20-40 mesh quartz sand and 40-80 mesh quartz sand in a mass ratio of (1-2):9.
[0024] According to the above scheme, the coarse aggregate is one or more of dolomite, porcelain white stone, glass sand, and crystal stone; and its particle size is 2-5mm.
[0025] According to the above scheme, the alkali-resistant glass fiber is water-soluble, has a length of 3-5 mm, and a diameter of 10-36 μm.
[0026] According to the above scheme, the toner is light gray, medium gray or dark gray; specifically, Bayer iron oxide or the like can be selected.
[0027] According to the above scheme, the defoaming agent can be a polyether or silicone defoaming agent.
[0028] According to the above scheme, the water reduction rate of the polycarboxylic acid water reducer is 25-30%.
[0029] The method for preparing the above-mentioned combined layer using terrazzo comprises the following steps:
[0030] 1) white cement, silica powder, calcium-silicon mineral admixture, white quartz sand, color powder, modified cellulose ether and defoamer weighed according to the proportion are mixed evenly, polycarboxylate water-reducing agent and water are added and stirred evenly to obtain slurry, alkali-resistant glass fiber and coarse aggregate are added to the obtained slurry and stirred evenly to obtain a terrazzo mixture for the combined layer;
[0031] 2) Spread the obtained mixture into the mold, compact it with a pressing plate, discharge the internal pores to improve the adhesion with the template and the surface density, and ensure that the stones are evenly distributed and close to the bottom surface. After compaction, spray the surface with mist water or acrylic emulsion, and use a defoaming roller to further defoam the surface. Finally, use a bubble film or a serrated anti-skid pad to roughen the slurry surface to ensure that the depth of the rough depression is 2 to 4 mm, and obtain the combined layer terrazzo material.
[0032] The combined layer terrazzo prepared according to the above scheme has a 28d compressive strength of >120MPa, a 0.5h fluidity loss of <20mm, an anti-sagging performance of <30mm at slopes of 20°, 50°, and 90°, a 28d bending resistance of >18MPa, and a 28d chloride ion diffusion coefficient of <3.0×10-14 m 2 ·s -1 , 200 freeze-thaw cycles without peeling.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. In the design of terrazzo cementitious materials, by adding nano-micron-sized silicon powder and calcium-silicon mineral admixtures of different particle size ranges, a continuous particle stacking model between multi-level materials is established to promote the closest stacking of the mixture, improve the density of the system, and ensure the good compressive and bending resistance of terrazzo.
[0035] 2. The present invention uses modified cellulose ether as an anti-sagging component and a reinforcing component to provide a certain thixotropy and effectively inhibit problems such as bubble defects: 1) The present invention introduces borate (B4O7 2- ), using the characteristics of boron as an electron-deficient atom, it replaces the lone pair of electrons on the hydroxyl oxygen atom in cellulose ether, causes cross-linking between alcohol hydroxyl groups, extends the molecular chain of cellulose ether, and forms a multi-dimensional network cross-linked compound, which will be adsorbed on the surface of cement particles, so that the slurry is subjected to the gripping force, that is, the slurry shows a thixotropic property that the consistency of the slurry decreases and the fluidity increases under the action of external force, and after the external force disappears, the consistency of the slurry gradually recovers and the fluidity decreases; and because of the borate (B4O7 2- ) oxygen atoms in the cellulose ether molecules are added to the hydroxyl groups on the cellulose ether molecules together with the boron atoms, further enhancing the association between the oxygen atoms and the water molecules in the slurry, making it easier for the water molecules to enter the network cellulose ether molecular chains and be constrained, thereby improving the stability of the cement in an alkaline environment and the anti-sagging property of the slurry. 2) Since the cellulose ether contains both hydrophilic groups (hydroxyl groups, ether groups) and hydrophobic groups (methyl groups, glucose rings), they are directionally adsorbed and enriched at the interface between gas and liquid in the cement slurry, improving the strength and toughness of the bubble liquid film, and having a certain air entraining effect. The present invention introduces borate (B4O7 2- ) replaces the hydrogen atoms in the hydroxyl group, weakens the adsorption of air, reduces the air entrainment effect of cellulose ether, and achieves the effect of inhibiting bubble defects; 3) There is still a small amount of free borate in the reaction system that combines with calcium ions in the slurry. On the one hand, the generated calcium borate can be adsorbed on the surface of some cement particles to form a complex, and the free water in the particles is released, which prolongs the initial setting time of the cement and improves the collapse resistance. On the other hand, due to the reduction of calcium ion concentration in the slurry, the amount of colloid generated by the condensation of calcium ions and sulfoaluminate ions produced by the hydration of C3A in the cement on the crystal surface is reduced, which is beneficial to crystal formation and promotes the hydration rate of cement particles, thereby improving the strength of terrazzo.
[0036] 3. The terrazzo slurry obtained by the present invention has good anti-sagging performance, and can maintain excellent anti-sagging effect on curved surface slopes greater than 50°, inclined surface slopes greater than 20, and even on vertical surface molds of 90°. At the same time, it has excellent construction performance. The surface of the terrazzo slurry after laying is slowly crusted, which can ensure sufficient casting of the upper structural layer and avoid the formation of cold joints that affect the overall structural performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 A schematic diagram of the cross-sectional structure of a curved surface (slope 50°) terrazzo curtain wall panel produced in Example 2 of the present invention;
[0038] Figure 2 A schematic diagram of the cross-sectional structure of a special-shaped (slopes at 20° and 90°) terrazzo curtain wall panel produced in Example 4 of the present invention;
[0039] Figure 3-Figure 5 Appearance diagram of some products produced by the present invention;
[0040] In the figure, 1. Terrazzo decorative layer; 2. Structural layer. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with specific embodiments. The examples are only used to explain the present invention and are not used to limit the scope of the present invention.
[0042] In the following embodiments, the white cement used is PW.52.5 white silicate cement with a whiteness of 85%; the activity index of silicon micropowder is 115%, the whiteness is 88%, and the mass content of SiO2 is 94%; the particle size of heavy calcium and quartz powder used in the calcium silicon mineral admixture is 325 mesh; the white quartz sand includes two particle sizes of 20-40 mesh and 40-80 mesh; the coarse aggregate is 3-5mm porcelain white stone and 2-3mm crystal stone; the alkali-resistant glass fiber is water-soluble, with a length of 3mm and an average diameter of 20μm; the color powder is Bayer iron oxide, specifically including three colors of light gray, medium gray and dark gray; the defoamer is the polyether defoamer DF-07 provided by Shanghai Yingshan New Material Technology Co., Ltd.; the water reduction rate of the polycarboxylic acid water reducer is 27%.
[0043] Example 1
[0044] A combined layer terrazzo, the preparation method of which comprises the following steps:
[0045] 1) Weighing of raw materials: weigh the raw materials according to the proportion, and the raw materials and their weight proportions are: 750 parts of white cement, 160 parts of silica powder, 120 parts of heavy calcium, 80 parts of quartz powder, 150 parts of 20-40 mesh white quartz sand, 850 parts of 40-80 mesh white quartz sand, 80 parts of porcelain white stone, 30 parts of crystal stone, 8 parts of alkali-resistant glass fiber, 10 parts of color powder (light gray), 174 parts of water, 4 parts of modified cellulose ether, 1.1 parts of defoaming agent, and 28 parts of polycarboxylic acid water reducer;
[0046] The preparation steps of the modified cellulose ether include:
[0047] (1) First, 10 parts of hydroxyethyl methyl cellulose ether are added to 60 parts of water; then 20 parts of 15wt% sodium carbonate solution are added as a catalyst, and magnetic stirring is performed in a 30°C constant temperature water bath, and then 0.6-0.8 parts of a borate-based crosslinking agent is added, and the mixture is heated to 50°C for a crosslinking reaction for 2-4 hours; after the reaction, a 75% acetic acid solution is used to adjust the pH to 7-8;
[0048] (2) aging the mixed solution obtained from the above reaction for 18 hours, filtering with suction, collecting the filter cake obtained, washing it with alcohol, drying it to constant weight, grinding it, and passing it through a 200-mesh sieve to obtain a powdered modified cellulose ether;
[0049] 2) The weighed white cement, silica powder, heavy calcium, quartz powder, white quartz sand, color powder, modified cellulose ether and defoamer are mixed evenly, and then polycarboxylate water reducer and water are added and stirred evenly, and finally alkali-resistant glass fiber, porcelain white stone and crystal transparent stone are added and stirred for 3-4 minutes to obtain terrazzo mixture;
[0050] 3) The obtained terrazzo mixture is laid into the mold and compacted by a customized pressing plate with a pressing surface having a circular protrusion with a diameter of 8mm, a spacing of 8-10mm, and a height of 6-8mm. The internal pores are discharged to improve the adhesion with the template and the density of the surface layer, while ensuring that the stones are evenly distributed and close to the bottom surface. After compaction, the surface is sprayed with mist water or acrylic emulsion, and the surface is further defoamed with a defoaming roller, and the thickness of the final decorative layer is controlled to be 10-15mm. Finally, the surface of the slurry is roughened with a bubble film or a serrated anti-skid pad to ensure that the depth of the rough depression is 2-4mm, and the combined layer of terrazzo material is obtained.
[0051] Example 2
[0052] A composite layer terrazzo, the preparation method of which is roughly the same as that of Example 1, except that: the raw materials and their weight proportions are: 800 parts of white cement, 130 parts of silica powder, 95 parts of heavy calcium, 70 parts of quartz powder, 200 parts of 20-40 mesh white quartz sand, 900 parts of 40-80 mesh white quartz sand, 85 parts of porcelain white stone, 30 parts of crystal stone, 6 parts of alkali-resistant glass fiber, 20 parts of color powder (medium gray), 182 parts of water, 4 parts of modified cellulose ether, 1.2 parts of defoaming agent, and 30 parts of polycarboxylic acid water reducer.
[0053] Example 3
[0054] A composite layer terrazzo, the preparation method of which is roughly the same as that of Example 1, except that: the raw materials and their weight proportions are: 850 parts of white cement, 100 parts of silica powder, 110 parts of heavy calcium, 95 parts of quartz powder, 180 parts of 20-40 mesh white quartz sand, 880 parts of 40-80 mesh white quartz sand, 80 parts of porcelain white stone, 25 parts of crystal stone, 8 parts of alkali-resistant glass fiber, 20 parts of color powder (medium gray), 188 parts of water, 5 parts of modified cellulose ether, 1.2 parts of defoaming agent, and 30 parts of polycarboxylic acid water reducer.
[0055] Example 4
[0056] A composite layer terrazzo, the preparation method of which is roughly the same as that of Example 1, except that: 800 parts of white cement, 120 parts of silica powder, 90 parts of heavy calcium, 90 parts of quartz powder, 200 parts of 20-40 mesh white quartz sand, 900 parts of 40-80 mesh white quartz sand, 90 parts of porcelain white stone, 30 parts of crystal stone, 6 parts of alkali-resistant glass fiber, 100 parts of color powder (dark gray), 197 parts of water, 5 parts of modified cellulose ether, 1.2 parts of defoaming agent, and 35 parts of polycarboxylic acid water reducer.
[0057] Comparative Example 1
[0058] A composite layer terrazzo material, the preparation method of which comprises the following steps:
[0059] 1) Weighing of raw materials: weigh the raw materials according to the proportion, and the raw materials and their weight proportions are: 840 parts of white cement, 150 parts of silicon powder, 150 parts of quartz powder, 150 parts of 20-40 mesh white quartz sand, 850 parts of 40-80 mesh white quartz sand, 80 parts of porcelain white stone, 20 parts of crystal stone, 8 parts of alkali-resistant glass fiber, 10 parts of Bayer light gray, 180 parts of water, 1.1 parts of defoamer, and 28 parts of polycarboxylate water reducer;
[0060] 2) After the weighed white cement, silica powder, heavy calcium, quartz powder, white quartz sand, color powder, porcelain white stone, crystal stone, and defoamer are mixed evenly, polycarboxylate water reducer and water are added and stirred to obtain slurry, and then alkali-resistant glass fiber is added and stirred for 1-2 minutes until the slurry is evenly mixed to obtain a terrazzo mixture;
[0061] 3) The obtained terrazzo mixture is laid into the mold and compacted by a customized pressing plate with a pressing surface having a circular protrusion with a diameter of 8mm, a spacing of 8-10mm, and a height of 6-8mm. The internal pores are discharged to improve the adhesion with the template and the density of the surface layer, while ensuring that the stones are evenly distributed and close to the bottom surface. After compaction, the surface is sprayed with mist water or acrylic emulsion, and the surface is further defoamed with a defoaming roller, and the thickness of the final decorative layer is controlled to be 10-15mm. Finally, the surface of the slurry is roughened with a bubble film or a serrated anti-skid pad to ensure that the depth of the rough depression is 2-4mm, and the combined layer of terrazzo material is obtained.
[0062] Comparative Example 2
[0063] A terrazzo material for combined layers, the preparation method of which is substantially the same as that of comparative example 1, except that:
[0064] 850 parts of white cement, 130 parts of silica powder, 100 parts of heavy calcium, 60 parts of quartz powder, 200 parts of 20-40 mesh white quartz sand, 900 parts of 40-80 mesh white quartz sand, 80 parts of porcelain white stone, 25 parts of crystal stone, 8 parts of alkali-resistant glass fiber, 20 parts of color powder (medium gray), 185 parts of water, 4 parts of hydroxyethyl methyl cellulose ether, 1.2 parts of defoamer, and 30 parts of polycarboxylate water reducer;
[0065] Comparative Example 3
[0066] A terrazzo material for combined layers, the preparation method of which is substantially the same as that of comparative example 1, except that:
[0067] 820 parts of white cement, 150 parts of silica powder, 100 parts of heavy calcium, 60 parts of quartz powder, 200 parts of 20-40 mesh white quartz sand, 900 parts of 40-80 mesh white quartz sand, 80 parts of porcelain white stone, 25 parts of crystal stone, 8 parts of alkali-resistant glass fiber, 100 parts of dark gray, 200 parts of water, 4 parts of hydroxyethyl methyl cellulose ether, 1 part of boric acid, 1.2 parts of defoamer, 35 parts of polycarboxylate water reducer;
[0068] Comparative Example 4
[0069] A terrazzo material for a combined layer, the preparation method of which is substantially the same as that of Comparative Example 1, except that: 830 parts of white cement, 150 parts of silica powder, 110 parts of heavy calcium, 70 parts of quartz powder, 200 parts of 20-40 mesh white quartz sand, 900 parts of 40-80 mesh white quartz sand, 80 parts of porcelain white stone, 24 parts of crystal transparent stone, 6 parts of alkali-resistant glass fiber, 20 parts of color powder (medium gray), 180 parts of water, 4 parts of modified cellulose ether, 1.1 parts of defoaming agent, and 33 parts of polycarboxylic acid water reducer;
[0070] The preparation steps of the modified cellulose ether include:
[0071] (1) First, 10 parts of hydroxyethyl methyl cellulose ether were added to 80 parts of water; then 15 parts of 8 wt% sodium hydroxide solution were added, and the mixture was stirred in a constant temperature water bath at 30° C. for 1 hour, and then 0.5 parts of ethylene oxide was added, and the mixture was heated to 60° C. for 3 hours for cross-linking reaction; after the reaction, the pH value was adjusted to 7-8 using 75% acetic acid solution;
[0072] (2) aging the mixed solution obtained from the above reaction for 18 hours, filtering with suction, collecting the filter cake obtained, washing it with alcohol, drying it to constant weight, grinding it, and passing it through a 200-mesh sieve to obtain a powdered modified cellulose ether;
[0073] The terrazzo material of a combined layer obtained from Examples 1-4 and Comparative Examples 1-4 was tested for fluidity, anti-sagging performance, 28d compressive strength, 28d flexural strength, 28d chloride ion permeability coefficient, and antifreeze performance. The anti-sagging performance test method is to place a plastic frame with an inner frame size of 300mm*300mm*10mm on a wooden board, spread the stirred terrazzo material into the frame, first press the slurry with the palm of your hand to ensure that the slurry is completely filled in the frame, then use a scraper to flatten it to ensure that the slurry thickness is 10mm, then remove the plastic frame, place the wooden board at slopes of 20°, 50°, and 90°, and measure the distance of the slurry flow after 60s to characterize the anti-sagging performance. If the distance of the slurry flow is longer, the anti-sagging performance is worse. On the contrary, it means that the anti-sagging performance is better.
[0074] Table 1 Performance test results of the products obtained from Examples 1-4 and Comparative Examples 1-3
[0075]
[0076]
[0077] It can be seen from Table 1 that the terrazzo material for the combined layer obtained by the present invention has good flow properties, anti-sagging properties, mechanical properties and durability, among which the 28d compressive strength is greater than 120MPa, the 0.5h fluidity loss is less than 20mm, the anti-sagging properties at slopes of 20°, 50° and 90° are all less than 30mm, the 28d bending resistance is greater than 18MPa, and the 28d chloride ion diffusion coefficient is less than
[0078] 3.0×10 -14 m 2 ·s -1 , there is no peeling after 200 freeze-thaw cycles; and the obtained terrazzo mixture can show the thixotropic property that the slurry consistency decreases and the fluidity increases under the action of external force, while after the external force disappears, the slurry consistency gradually recovers and the fluidity decreases.
[0079] Comparative Example 1 does not add modified cellulose ether, and has poor anti-sagging performance. It has an excellent flowing effect on an inclined plate with a certain slope, so that the slurry flows from a high slope to a low slope, resulting in a slurry thickness of less than 10 mm at a high slope and much greater than 10 mm at a low slope, which makes the thickness of the decorative layer uneven. Polishing the thin part will expose the structural layer, seriously affecting the appearance of the terrazzo.
[0080] Comparative Example 2 uses unmodified cellulose ether, which has good anti-sagging effect, but poor slump retention effect, low strength and poor durability. On the one hand, due to the air entraining effect of cellulose ether itself, the density of the slurry decreases, affecting the strength and durability.
[0081] Comparative Example 3 uses unmodified cellulose ether and boric acid, and the anti-sagging effect is slightly improved, but the cellulose ether has poor stability and a large amount of air entrainment. The adverse effects can be slightly offset by the introduction of boric acid alone, but the strength and durability are reduced compared with the examples.
[0082] Comparative Example 4 uses epichlorohydrin to modify cellulose ether. Although the anti-sagging effect of the slurry can be improved to a certain extent, the slump retention performance of the slurry and the terrazzo strength are inferior to those of the embodiment.
[0083] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.
Claims
1. A composite layer terrazzo, characterized in that: The components and their weight proportions include: 750-850 parts of white cement, 100-160 parts of silicon micropowder, 150-220 parts of calcium silicon mineral admixture, 900-1100 parts of white quartz sand, 100-120 parts of coarse aggregate, 5-10 parts of alkali-resistant glass fiber, 10-100 parts of color powder, 170-200 parts of water, 4-6 parts of modified cellulose ether, 1-1.5 parts of defoaming agent, and 25-35 parts of polycarboxylic acid water reducer; the modified cellulose ether is borate cross-linked modified cellulose ether.
2. The combined layer terrazzo according to claim 1, characterized in that: The preparation steps of the modified cellulose ether are as follows: (1) adding cellulose ether to water, adding a catalyst and stirring at room temperature, then adding a borate-based crosslinking agent and heating to carry out a crosslinking reaction; then adjusting the pH value of the resulting solution system to be neutral or weakly alkaline; (2) The mixed solution obtained from the above reaction is aged and filtered, and the filter cake is collected and washed with alcohol, dried to constant weight, ground and sieved to obtain powdered modified cellulose ether.
3. The combined layer terrazzo according to claim 2, characterized in that: The borate-based cross-linking agent is boric acid or borax; the catalyst is sodium carbonate or sodium hydroxide.
4. The combined layer terrazzo according to claim 2, characterized in that: The temperature used for the cross-linking reaction is 50-60°C and the time is 2-4h.
5. The combined layer terrazzo according to claim 2, characterized in that: The aging time is 16-24h.
6. The combined layer terrazzo according to claim 2, characterized in that: The mass ratio of the cellulose ether to the borate-based crosslinking agent is 10:(0.6-0.8).
7. The combined layer terrazzo according to claim 1, characterized in that: The white cement is white silicate cement, with a strength grade not less than 52.5 and a whiteness of ≥84%; the activity index of the silicon micropowder is greater than 105%, the whiteness is greater than 87%, and the SiO2 mass content is greater than 92%; the calcium-silicon mineral admixtures include heavy calcium and quartz powder.
8. The combined layer terrazzo according to claim 1, characterized in that: The coarse aggregate is one or more of dolomite, porcelain white stone, glass sand and crystal stone; its particle size is 2-5mm; the alkali-resistant glass fiber is water-soluble, its length is 3-5mm and its diameter is 10-36μm.
9. The combined layer terrazzo according to claim 1, characterized in that: The defoamer is a polyether or silicone defoamer; the water reduction rate of the polycarboxylic acid water reducer is 25-30%.
10. The method for preparing the combined layer terrazzo according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) white cement, silica powder, calcium-silicon mineral admixture, white quartz sand, color powder, modified cellulose ether and defoamer weighed according to the proportion are mixed evenly, polycarboxylate water-reducing agent and water are added and stirred evenly to obtain slurry, alkali-resistant glass fiber and coarse aggregate are added to the obtained slurry and stirred evenly to obtain a terrazzo mixture for the combined layer; 2) Spread the obtained mixture into a mold, compact it with a pressing plate, spray mist water or acrylic emulsion on the compacted surface for defoaming treatment, and finally perform roughening treatment to obtain a combined layer of terrazzo.
Citation Information
Patent Citations
Production method taking UHPC as binding material for special-shaped waterstone
CN108656309A
Plastic terrazzo material and preparation method thereof
CN115093638A